Anthropometric Measurements and their Relationship to the Level of Achievement among Junior Swimmers in Jordan (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
The study aimed to identify anthropometric measurements (body mass, body height, arm’s length, leg’s length, chest circumference, and waist circumference) and their relationship to the level of achievement among junior swimmers in Jordan. The researcher used the descriptive approach as it suits the study. The sample of the study consisted of 36 juniors from Al-Hussein Youth City Club swimming pool and the International Academy simming pool, both in Amman. The samples were selected by a Complete Census method. The anthropometric variables were measured by a medical scale, a measure tape, and, to measure the level of achievement represented by the time of the belly crawl swimming for a distance of 25 meters, a stopwatch.To analyze the data statistically, the following statistical methods were used: arithmetic mean, standard deviation, skew coefficient, Pearson correlation coefficient, and regression analysis. The study concluded that body mass is the only variable that can predict the time of belly crawl swimming among juniors in Jordan. The researcher recommended the need to rely on body mass in selecting junior swimmers for the goal of an achievement in belly crawl swimming.
Keywords: level of achievement.; anthropometric measurements